Evaluation of thermal performance through development of a PCM-based thermal storage control system integrated unglazed transpired collector in experimental pig barn. (December 2019) - Moon, Byeong Eun; Kim, Hyeon Tae
Highlights: A PCM-based thermal storage control system integrated UTC was applied to pig barns. The correlation between the solar radiation and UTC efficiency was verified ( R 2 = 0.58 ). The heat storage efficiency of up to 85%, a daily average of 22% were verified. The average energy generation in the UTC plenum was 13, 548.21 kcal/day. The average storage and release energies were 7739.78 and 1793.47 kcal/day. Abstract: The application of unglazed transpired collectors (UTCs) in livestock barns is an excellent solution for air ventilation in winter, for reducing structural energy loss, and for improving indoor air quality. However, thermal energy generated within specific periods may overheat the inside of the livestock barns. Thus, this study developed and applied a PCM-based thermal control system for saving and utilizing excess thermal energy generated by the application of a UTC in a experimental pig barn, through which the corresponding temperature deviation and the thermal performance of the thermal storage system are analyzed. During the experimental period, the UTC plenum temperature rose up to 65 °C, which is approximately 35 °C higher than that of the outdoor air throughout the day. The nonlinear correlation between the amount of solar radiation and UTC efficiency was verified during the experimental period ( R 2 = 0.58 ). Throughout the heat storage stage, the excess heat energy generated at the UTC plenum had a verified heat storage efficiency of up to 85%, a daily average of 22%, and an effect of a temperature difference of the PCM of 22.6 °C. Additionally, an average daily efficiency of 57% and an effect of a temperature increase of 13.8 °C compared to the outdoor temperature were verified through the heat release stage. The average thermal storage time was about 5 h and 50 min and the average release time was about 2 h and 33 min. During the experimental period, the average energy generation in the UTC plenum was 13, 548.21 kcal/day and the average storage and release energies were 7739.78 and 1793.47 kcal/day, respectively.